Baseline characteristics and clinical symptoms related to respiratory viruses identified among patients presenting with influenza-like illness in primary care. (September 2019) - Souty, C.; Masse, S.; Valette, M.; Behillil, S.; Bonmarin, I.; Pino, C.; Turbelin, C.; Capai, L.; Vilcu, A.M.; Lina, B.; van der Werf, S.; Blanchon, T.; et al.
Abstract: Objectives: We aimed to identify patients' clinical characteristics associated with respiratory viruses identified among patients presenting with influenza-like illness (ILI). Methods: A sample of patients of all ages presenting with ILI was included by physicians of the French Sentinelles network during two seasons (2015/16 and 2016/17). Nasopharyngeal samples were tested for the presence of influenza virus (IV), respiratory syncytial virus (RSV), human rhinovirus (HRV) and human metapneumovirus (HMPV). Patients' characteristics associated with each of the four virus classes were studied using multivariate logistic regressions. Results: A total of 5859 individuals were included in the study: 48.0% tested positive for IV, 7.9% for HRV, 7.5% for RSV and 4.1% for HMPV. Cough was associated with IV (OR 2.14, 95% CI 1.81–2.52) RSV (OR 2.52, 95% CI 1.75–3.74) and HMPV detection (OR 2.15, 95% CI 1.40–3.45). Rhinorrhoea was associated mainly with HRV detection (OR 1.75, 95% CI 1.34–2.32). Headache was associated with IV detection (OR 1.75, 95% CI 1.34–2.32), whereas absence of headache was associated with RSV and HMPV detection. Dyspnoea was associated with RSV detection (OR 2.33, 95% CI 1.73–3.12) and absence of dyspnoea with IV detection. Conjunctivitis was associated with IV detection (OR 1.27, 95% CI 1.08–1.50). Some associations were observed only in children: dyspnoea and cough with RSV detection (age <5 years), conjunctivitis with IV detection (age <15 years). Period of onset of symptoms differed among aetiological diagnoses. Seasonal influenza vaccination decreased the risk of IV detection (OR, 0.67, 95% CI 0.51–0.86). Conclusions: This study allowed the identification of symptoms associated with several viral aetiologies in patients with ILI. A proper knowledge and understanding of these clinical signs may improve the medical management of patients.